Territorios educativos y compromiso académico: percepciones de un grupo de futuros formadores - Rigo, Daiana Yamila (2025)
This study unfolds in two stages. The first stage aims to describe the diverse and expanded experiences that students enrolled in the Teacher Training and Bachelor’s Degree in Early Childhood Education undergo throughout their formative process. The second stage explores the most frequently mentioned educational territories—university classrooms, professional practices, and socio-community practices—to understand students’ perceptions of how these environments foster academic engagement. A quantitative research design was employed, with a total sample of 120 future educators from the National University of Río Cuarto, who voluntarily completed two instruments: an ad hoc questionnaire and a standardized survey. The results indicate that each educational territory promotes different dimensions of academic engagement and complements the others.